Arráncame la vida, de Ángeles Mastretta: reimaginar a la mujer en la literatura - Chaves Alfaro, Iris (2013)
The novel Arráncame la vida, by the mexican writer Angeles Mastretta, is an example of literature that proposes new ways of imaging the woman and, as a consequence, the social relations. This article analyzes this novel from the perspective of today´s separating discourse of patriarchal culture and the social imaginary vision.